Surface Heterogeneity at the Solid-Gas Interface of Hydrophilic Solids Modified by Water-Repellent Molecules - F. Villiéras; M. Chamerois; J. Yvon; J.M. Cases (Adsorption Science & Technology)
The surface heterogeneity of a hydrophilic calcium carbonate (calcite) at the solid-gas interface was studied before and after modification by the adsorption of different amounts of a water-repellent molecule (WRM). The surface heterogeneity was analysed using nitrogen, argon and water as molecular probes. Low-pressure adsorption techniques coupled with derivative isotherm summation (DIS) analysis of the experimental curves gave quantitative information on the decrease in the calcite surfaces and the increase in the WRM surfaces. The modelling results enabled the monolayer capacity for WRMs as measured by argon adsorption to be correlated with the disappearance of calcite surfaces and the disappearance of high-energy adsorption sites as measured by nitrogen adsorption. In addition, the argon results suggested that WRMs first adsorb on argon low-energy carbonate faces and then on low- and high-energy faces. With water, the adsorption energy distribution remained unchanged in shape, indicating that this molecule can diffuse into the adsorbed layer between and around the adsorbed hydrophilic heads of the WRMs and thereby interact directly with the carbonate surface.